Access to international markets through joint venture. (11th May 2004) - Connor, Tom; Ballentine, Norman
This article considers the case of Hayward Tyler, a UK based manufacturer of engineered pumping equipment. The company was considering establishing a joint venture in Malaysia to produce equipment for the Asian market. This industry is primarily confined to the industrialised countries and little dispersion of manufacture has yet occurred to the developing economies. The article considers Hayward Tyler's approach to this project on a resource constrained basis and the issues and management steps identified from the company's research as fundamental to optimising the probability of a successful venture. The article concludes in the context of the economic crisis which afflicted the Asian region in 1998.